Evaluasi Kualitas Media Flyer Paket Informasi Kesehatan Keluarga (PINKESGA) Sebagai Alat Bantu Edukasi Penyakit Hipertensi Pada Masyarakat di Puskesmas Ciputat Tahun 2023 - Halimah, Annisa; Alkaff, Raihana Nadra (Journal of Religion and Public Health, 2023)
AbstractSeveral efforts have been made by the Ciputat Health Center in dealing with hypertension such as organizing posbindu, home visits to monitor the elderly, NGIDER Sehat, PIS-PK, and outreach to the community. One of the health education aids used is the flyer (PINKESGA) contained in the Program (PIS-PK). PINKESGA which contains information on 12 healthy indicators, is conveyed to the public when officers visit people's homes. However, field results show that there are still officers who do not carry and use PINKESGA during visits to people's homes. This study used a qualitative study approach to evaluate the quality of the PINKESGA flyer as an educational tool for hypertension in the community at the Ciputat Health Center in 2023. Data and information were collected through in-depth interview techniques with 6 main informants and 5 supporting informants. Technically, the quality of the PINKESGA flyer still has deficiencies in terms of confusing illustrations and inappropriate layouts. The quality of the PINKESGA flyer message content is also not good because the information contained is incomplete. Instructionally, the PINKESGA flyer has been able to raise the motivation and ability to manage hypertension in the community. It is recommended to add a QR code to the flyer so that it can be accessed online, avoid excessive color and letter variations and it is necessary to socialize health center staff about the importance of using the PINKESGA flyer tool. Keywords: Flyer, Hypertention, PINKESGA